Analysis of Phraseological Units in Prima PLUS Textbooks for German as a Foreign Language - Stanojević Veselinović, Marija M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Phraseological units are an integral part of any language and play a crucial role in developing students' linguistic competence. Their use facilitates more natural, fluent, and expressive communication. However, learning phraseological units can pose a challenge, particularly in the early stages of acquiring a foreign language. Therefore, this study analyzes the presence, classification, didactic processing, and function of phraseological units in the Prima PLUS textbooks, designed for learning German as a second foreign language in the second cycle of primary education in Serbia. The aim of the research is to determine the extent to which phraseological units are represented in the selected textbooks, the types of phraseological units included, how they are presented, and how they contribute to the development of students' language skills.For the purposes of this study, a series of textbooks (Prima PLUS A1.1, Prima PLUS A1.2, Prima PLUS A2.1, and Prima PLUS A2.2) was selected. The primary criterion for their selection was their status as accredited textbooks in Serbia. Another reason for their selection pertains to the publisher, Data Status, one of the most prominent publishing houses in Serbia. Additionally, these textbooks have been widely used for years in the majority of primary schools in Serbia for teaching German as a second foreign language. Therefore, analyzing the presence and didactic treatment of phraseological units in these textbooks appeared to be a justified and relevant research endeavor. Since the aim of this study was to determine the presence of phraseological units in textbooks, classify them, and analyze how they are integrated into textbook content, both quantitative and qualitative content analysis methods were applied. The significance of this study is both theoretical and practical, as phraseological units and their classification are clearly defined, with particular emphasis on routine formulas. Furthermore, the results of the analysis regarding the presence and implementation of phraseological units highlight opportunities for improving the systematic presentation and integration of these units through exercises and their application in various contexts within the Prima PLUS textbooks.
Keywords: Prima PLUS textbooks; German as a second foreign language; phraseological units; collocations; routine formulas